Correlation between facial measurements and vertical dimension of occlusion among Tunisian populations: An anthropometric study - Imed Ouni; Rania Jebali; Sinda Amar; Lamia Mansour (Tabriz University of Medical Sciences, 2022)
Background. Establishing an accurate occlusal vertical dimension (OVD) is a crucial clinical step during full-mouth rehabilitation. Various techniques have been suggested to evaluate OVD, but none of them is practically reliable, and each one has its shortcomings. The correlation between facial proportions and the lower third of the face is a reliable method but needs to be verified in many ethnic groups. Therefore, this study aimed to determine the correlation between OVD and various facial measurements in a Tunisian ethnic group. Methods. A cross-sectional study was conducted between November 2020 to January 2021. The participants were randomly selected from dental students, dental surgeons, and the patients referring to the University Dental Clinic for dental treatments. Seven facial measurements were clinically recorded using a digital caliper. The correlation between OVD and facial measurements was analyzed using Spearman's coefficient and linear regression analysis. Results. A total of 201 dentate participants (134 females and 67 males) were included in the study. The mean OVD in male subjects was higher (67.60±4.49) compared to female subjects (60.72±3.84). The total facial height was positively correlated with OVD in both genders. OVD was statistically correlated with the height of the upper lip. This correlation was highly significant in males while it was weak in the female group. Conclusion. Facial proportions and linear equations are non-invasive, simple, and reliable methods to predict OVD, especially in males.